2022
DOI: 10.1007/s12035-022-03087-9
|View full text |Cite
|
Sign up to set email alerts
|

Amorfrutin B Protects Mouse Brain Neurons from Hypoxia/Ischemia by Inhibiting Apoptosis and Autophagy Processes Through Gene Methylation- and miRNA-Dependent Regulation

Abstract: Amorfrutin B is a selective modulator of the PPARγ receptor, which has recently been identified as an effective neuroprotective compound that protects brain neurons from hypoxic and ischemic damage. Our study demonstrated for the first time that a 6-h delayed post-treatment with amorfrutin B prevented hypoxia/ischemia-induced neuronal apoptosis in terms of the loss of mitochondrial membrane potential, heterochromatin foci formation, and expression of specific genes and proteins. The expression of all studied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The molecular mechanism of interaction between BCL2 and BAX relies on BCL2-induced conformational changes of BAX that prevent its oligomerization, which is necessary to form pores in the mitochondrial membrane (Dlugosz et al 2006 ); in this way, the decrease in the BCL2/BAX ratio induces apoptosis. Upregulation of BCL2 in the ischemic model may seem surprising, but similar effects have already been observed in other cellular models of brain hypoxia and ischemia as well as Alzheimer’s and Huntington’s diseases (Satou et al 1995 ; O’Barr et al 1996 ; Kitamura et al 1998 ; Sulejczak et al 2004 ; Sassone et al 2013 ; Wnuk et al 2021a , 2021b ; Przepiórska et al 2023 ). The observed phenomenon is likely a survival mechanism.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The molecular mechanism of interaction between BCL2 and BAX relies on BCL2-induced conformational changes of BAX that prevent its oligomerization, which is necessary to form pores in the mitochondrial membrane (Dlugosz et al 2006 ); in this way, the decrease in the BCL2/BAX ratio induces apoptosis. Upregulation of BCL2 in the ischemic model may seem surprising, but similar effects have already been observed in other cellular models of brain hypoxia and ischemia as well as Alzheimer’s and Huntington’s diseases (Satou et al 1995 ; O’Barr et al 1996 ; Kitamura et al 1998 ; Sulejczak et al 2004 ; Sassone et al 2013 ; Wnuk et al 2021a , 2021b ; Przepiórska et al 2023 ). The observed phenomenon is likely a survival mechanism.…”
Section: Discussionmentioning
confidence: 52%
“…Measurement of mitochondrial membrane potential was performed using a JC-10 Assay Kit (Abcam, Cambridge, UK) as previously described (Przepiórska et al 2023 ). JC-10 transpires into mitochondria and polymerizes there in cells with proper mitochondrial membrane potential, forming aggregates with characteristic red fluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…Amorfrutin B is an SPPARγM that we recently demonstrated for the first time to be a promising neuroprotective compound in cellular models of stroke and perinatal asphyxia. Indeed, we showed that post-treatment of mouse neurons with amorfrutin B caused neuroprotection that relied on its inhibitory action on hypoxia/ischemia-induced apoptosis, autophagy and oxidative stress as well as on normalization of the epigenetic status of neuronal cells (Wnuk et al 2021a , Wnuk, Przepiórska et al 2021 ; Przepiórska et al 2023 ). Although neuronal mechanisms of amorfrutin B-evoked neuroprotection have been identified, none of them reflects the action of the compound on microglia known to play a pivotal role in the response of brain tissue to hypoxic and ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Our team was the first to demonstrate that amorfrutin B protects primary mouse neurons against hypoxia/ischemia-induced cell damage, even when applied 6 h after injury. We showed that this PPARγ-specific neuroprotection relies on epigenetic modifications, as well as inhibition of apoptosis, autophagy and oxidative stress (Wnuk et al 2021a , Wnuk, Przepiórska et al 2021 ; Przepiórska et al 2023 ). The strong effectiveness of amorfrutin B in protecting cells against hypoxia/ischemia suggests that this compound has the potential to adjust to clinical standards, however, it is unknown whether its possible use may be applicable to modulating microglial immunoreactivity in pathological conditions caused by hypoxia and ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelming evidence has demonstrated that autophagy is required for the development, differentiation, tissue remodeling, and immune regulation of various organisms [10,11]. Therefore, autophagic dysfunction or impaired autophagic degradation is associated with the pathogenesis of many human diseases, including infections, cancer [12], neurodegeneration [13], aging [14], heart disease [15], and muscle disease [16].…”
Section: Introductionmentioning
confidence: 99%